Inkjet printed pressure sensing platform for postural imbalance monitoring - Cruz, Sílvia Manuela Ferreira (2015)
In this paper, a low-cost printed pressure sensing platform is presented. The sensing platform consists of a flexible printed circuit board manufactured using conventional technology (defining the electrical connections and the capacitors dimensions) together with two flexible polymeric membranes made from a thermoplastic elastomer (TPU) printed with conductive ink Poly (3,4-ethylenedioxythiophene)-poly (styrenesulfonate) for definition of the electrodes. A capacitance-to-digital converter is used to measure the capacitance of the sensors, and a graphical interface in MATLAB allows real-time visualization of data. A prototype sensing platform was designed, fabricated, and tested. The capacitive sensors show a sensitivity of 50 fF/kPa in the region of operation, a noise of 1.2 fF/root Hz, and a stability of better than 1.5% full scale. The proposed pressure sensor platform has the potential to integrate multiple sensing parameters for ubiquitous environment monitoring.